Inoculação de DL-metionina em ovos embrionados de matrizes avícolas - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This study aimed to evaluate the use of DL-methionine to in ovo feeding of chick embryos. The study was conducted at the facilities of Poultry Technology Laboratory of Poultry Sector of the Department of Animal and Plant Production, College of Agrarian Sciences, Federal University of Amazonas, Manaus, Amazonas, Brazil. A total of 224 fertile eggs from Rhode Island Red breeders (35 weeks of age) were used. The experimental design was completely randomized with the treatments constituted by two controls and five solutions containing DL-methionine levels with 32 replicates (eggs) each. Data collected were subjected to polynomial regression at 5% of significance. The incubation yields, chick / egg ratio, serum biochemical parameters and development of gastrointestinal tract (directly related organs and regions) of the hatch chicks were evaluated. Statistical analysis was performed using SAS software (2008), where the data collected were submitted to analysis of variance and the estimates of the treatments were analysed by polynomial regression at 0.01 and 0.05 of significance. The results of this study indicate that up to 1.0% of DL-methionine can be used for in egg feeding for chick embryos, providing higher birth weight, greater yolk sac weight, increased goblet cell numbers in crypts of small intestine and the villi of the large intestine, and better development of the mucous layer of the small and large intestine.
Keywords: Alimentação in ovo; Aminoácido; Biotecnologia; Desenvolvimento embrionário; CIÊNCIAS AGRARIAS: ZOOTECNIA